Treatment Effectiveness and Tolerability of Long-term Adjuvant First- and Second-Generation Epidermal Growth Factor Receptor Tyrosine Kinase Inhibitor at Different Doses in Patients With Stage IIA–IIIB Epidermal Growth Factor Receptor-Mutated Lung Adenocarcinoma: A Retrospective Study - Ye, Jing-Ren; Chen, Pei-Hsing; Chuang, Jen-Hao; Lin, Mong-Wei; Tsai, Tung-Ming; Hsu, Hsao-Hsun; Chen, Jin-Shing (Frontiers in Surgery, 2022)
Background: For patients with epidermal growth factor receptor (EGFR)-mutated lung cancer who undergo surgery, adjuvant tyrosine kinase inhibitor (TKI) therapy is an option. This article aimed to discuss the long-term safety and efficacy of TKI treatment in the real world data. Methods: From January 2011 to May 2020, patients with stage II-III EGFR-mutated adenocarcinoma who underwent cancer resection surgery in a single center were enrolled. The primary endpoint was disease relapse, and the secondary endpoint was overall survival. There are 30 patients was included in the study. In our study, all patients underwent complete resection using video-assisted thoracoscopic surgery. The patients were divided into a dose interruption (prolonged interval use) group and non-dose adjustment group. Results: The patients’ pathological stages were II–III. The initial EGFR-TKIs were mostly gefitinib (n=25, 83%), and the others were erlotinib (n=3, 10%) and afatinib (n=2, 6%). The mean disease-free survival (DFS) rate was 53.3 months. The 2-year and 5-year DFS rate was 90.0% and 73.3%, respectively. The median TKI treatment duration in this study was 44.5 months (range, 6–133 months), which was the longest in the literature review. Of these patients, nine had dose interruption. We compared the two groups and found no treatment differences between them. There were no significant side effect potentials between both groups. Conclusion: To our knowledge, this study provides the longest experience of TKI in patients with resected EGFR mutations and also provided a dose reduction strategy (prolonged medication interval) for patients who had intolerable side effects.